Chronic idiopathic urticaria and thyroid autoimmunity: Perplexing association - S Yadav; A J Kanwar; D Parsad; R W Minz (Wolters Kluwer Medknow Publications, 2013)
Background: Autologous serum skin test (ASST) is the most commonly used laboratory test to differentiate chronic autoimmune urticaria patients from chronic idiopathic urticaria patients without autoantibodies. Thyroid autoimmunity is the original paradigm for autoimmune disease in general and many previous studies show increased prevalence of thyroid autoantibodies and deranged thyroid hormone profile in chronic idiopathic urticaria patients. Aim: To find the association between thyroid autoimmunity and chronic autoimmune urticaria, if any. Materials and Methods: The chronic idiopathic urticaria patients were divided into two subgroups based on autologous serum skin test. Thyroid autoantibodies were estimated in 40 patients each of ASST positive and ASST negative groups. Further, thyroid hormone profile was done in cases with significant titers of thyroid autoantibodies. Forty patients, who had never suffered from urticaria, represented the control group. Results: The prevalence of thyroid autoantibodies did not differ significantly among the ASST positive (20%) and ASST negative patients (15%). The control group had low prevalence of these autoantibodies (5%). Conclusion: The almost equal prevalence of thyroid autoantibodies in two subgroups of chronic idiopathic urticaria patients suggests possibly the same etiopathogenesis of the two subgroups. The two subgroups probably form a continuum, or even may be the same entity.